The Nonproliferation Stewardship Program [version 1; peer review: 3 approved] - Heather Dion; Michael Miller; Ashley Shields; Randy Ngelale; Laura Maggos; Janine Lambert; Eddy Banks; Brienne Seiner (Nuclear Science and Technology Open Research)
The National Nuclear Security Administration (NNSA)’s Office of Defense Nuclear Nonproliferation (DNN) initiated the Nonproliferation Stewardship Program (NSP) in 2020 to provide an enduring pipeline of nonproliferation subject matter experts to Department of Energy (DOE)/NNSA laboratories, sites, and plants. This program provides nonproliferation-relevant science and technology opportunities through a modernized facility infrastructure. This paper provides an overview of NSP, highlights ongoing efforts in uranium and plutonium processing, and describes examples of hands-on experimental work and associated modeling and simulation.